Physical activity may a probably protective factor for postoperative delirium: the PNDABLE study - Kong, Jian; Lin, Xu; Wang, Bin; Xu, Shanling; Wang, Yuanlong; Hua, Shuhui; Gong, Hongyan; Dong, Rui; Lin, Yanan; Li, Chuan; Bi, Yanlin (Frontiers in Aging Neuroscience, 2024)
This study aims to explore the relationship between physical activity (PA) and postoperative delirium (POD).We selected 400 patients from the Perioperative Neurocognitive Disorder and Biomarkers Lifestyle (PNDABLE) database, and the patients in the PNDABLE database were sampled and tested Alzheimer's biomarkers. The diagnosis of POD was made using the Confusion Assessment Scale (CAM) and the severity was assessed using Memorial Delirium Assessment Scale (MDAS). Mini-Mental State Examination (MMSE) scale was used to detect the mental state of the patients.Enzyme-linked immunosorbent assay (ELISA) was used to detect the level of preoperative cerebrospinal fluid (CSF) biomarkers, such as amyloid β plaque 42(Aβ42), total tau protein(T-tau), and phosphorylated tau protein(P-tau). Logistic regression, sensitivity analysis, and Post hoc analysis were used to explore the relationship between risk and protective factors on POD. We used the mediating effect to explore whether PA mediates the occurrence of POD through CSF biomarkers.The incidence of POD was 17.5%. According to our research, the consequence prompted that PA might be the protective factor for POD (OR: 0.336 95CI 0.206-0.548 P<0.001). The result of logistic regression revealed that CSF biomarker Aβ42 (OR: 0.997 95CI 0.996-0.999 P<0.001) might be a protective factor against POD, and the T-tau (OR: 1.006 95CI 1.003-1.009 P=0.001) and P-tau (OR: 1.039 95CI 1.018-1.059 P<0.001) might risk factors for POD. Sensitivity analysis confirmed the correlation between PA and CSF biomarkers in the patients with POD. Mediation effect analysis showed that PA may reduce the occurrence of POD partly through CSF biomarkers, such as Aβ42 (proportion: 11%, P<0.05), T-tau (proportion: 13%, P<0.05), and P-tau (proportion:12%, P<0.05).Physical activity (PA) is probably a protective factor for postoperative delirium (POD) and may exert a mediating effect through cerebrospinal fluid (CSF) biomarkers.